Development of Sparkol Videoscribe-Based Animated Video Learning Media on the Subject of IPAS Material Changes in the Form of Substances - Elisa Ratna Dewi; Dewi Nilam Tyas (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to develop learning media  Sparkol Videoscribe-based animated video that is feasible and effective in improving the cognitive learning outcomes of students in the subject of Natural and Social Sciences (IPAS) material on changes in the form of substances in class IV SDN 1 Tambakrejo, Grobogan Regency. This study uses a quantitative approach with a development research method (R&D) based on the Borg and Gall development model. The data collection techniques used include tests (pretest and post test) and non-tests (observation, interview, documentation, and questionnaire) with research subjects 1 material expert, 1 media expert, teachers as practitioners and students totaling 9 on small-scale trials and 25 on large-scale trials. The results of validation by expert validators showed a high level of material feasibility and learning media design, namely 90.62% and 93.30%. This learning media is proven to be effective in improving student learning outcomes, indicated by the results of the t-test of the pretest and posttest values with sig (2-tailed) 0.000 < 0.005 and 0.004 < 0.005 while in the N-gain test there was an increase from 64.06 to 77.62 with a difference of 13.56 with a percentage of 0.39% including into the "medium" criteria. Thus, it can be concluded that it has been successfully developed Sparkol Videoscribe-based animated video learning media that is feasible and effective to use in learning to improve students' cognitive learning outcomes in IPAS subjects on material changes in the form of substances.